2011
DOI: 10.1007/s11136-011-9928-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties and gender invariance of the Chinese version of the self-report pediatric quality of life inventory version 4.0: short form is acceptable

Abstract: The Chinese version of the PedsQL is a relatively reliable and valid instrument, and the PedsQL short form showed a better construct validity than did the full form. Measurement across gender was invariant; therefore, the comparisons of quality of life between boys and girls were appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 25 publications
5
56
1
Order By: Relevance
“…Thus, the halo effect raises the heterotraitmonomethod values above those of the monotrait-heteromethod values. The CFA models in the present study demonstrated the method effects, and supported that the discriminant and convergent validity of the PedsQL is valid and reliable for measuring children's QoL in various language versions (e.g., Chan et al 2005;Huguet and Miró 2008;Kobayashi and Kamibeppu 2010;Upton et al 2005), including the Chinese version used in Taiwan (Lin et al 2012a(Lin et al , 2013a. However, although both parent-proxy reports and child-self reports are used, most of these studies examine the validity of PedsQL separately for these two methods.…”
Section: Methods Effects and The Construct Validity Of The Pedsqlsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, the halo effect raises the heterotraitmonomethod values above those of the monotrait-heteromethod values. The CFA models in the present study demonstrated the method effects, and supported that the discriminant and convergent validity of the PedsQL is valid and reliable for measuring children's QoL in various language versions (e.g., Chan et al 2005;Huguet and Miró 2008;Kobayashi and Kamibeppu 2010;Upton et al 2005), including the Chinese version used in Taiwan (Lin et al 2012a(Lin et al , 2013a. However, although both parent-proxy reports and child-self reports are used, most of these studies examine the validity of PedsQL separately for these two methods.…”
Section: Methods Effects and The Construct Validity Of The Pedsqlsupporting
confidence: 77%
“…The Chinese version of the short form PedsQL is a validated 15-item questionnaire for children aged 8 to 12 years (Lin et al 2012a(Lin et al , 2013a. In addition, evidence supports the notion that comparisons between parents' and children's reports are meaningful, that is, that measurement equivalence has been established across parent reports and child reports of PedsQL (Lin et al 2013a).…”
Section: Samplementioning
confidence: 90%
“…21 An ICC value >0.75 suggest satisfactory internal consistency and test-retest reliability, respectively. 22 In our study it was 0.753, however some studies suggest 0.850 for this value. 23 However, this value may be due to the likelihood of a 7-point likert scale being used in the original.…”
Section: Discussioncontrasting
confidence: 64%
“…Therefore, their health outcomes are generally lower than that of the general population (Hegarty, Baldessarini, Tohen, Waternaus, & Oepen, 1994;Su, Ng, Yang, & Lin, 2014). The subjective quality of life (SQoL) is one of the most important outcomes among the impaired health-related outcomes for people with schizophrenia, with growing interest for healthcare providers (Lin et al, 2012). Many studies (Carpenter & Buchanan, 1994;Hegarty et al, 1994;Hooley, 2010;Yen et al, 2008) have shown that an individual's SQoL, including physical and psychological aspects, is impaired in people with a mental illness such as schizophrenia.…”
mentioning
confidence: 99%